Implementasi Sistem Keuangan Desa (Siskeudes) dalam Pengelolaan Apbdes di Desa Kedungjaya Kabupaten Bekasi - Hasby Rizal Machfuz; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Application Sistem Keuangan Desa or SISKEUDES is a tool specifically for village governments in managing village finances starting from the planning, budgeting, administration, and bookkeeping stages. However, in its implementation there are still many obstacles such as human resources (HR) who do not understand the SISkeudes application, reports have not been inputted into the system and still use manual reporting, inadequate facilities and infrastructure, and application errors when input data is used. . The purpose of this study was to determine the implementation of Siskeudes in Kedungjaya Village. This study used qualitative research methods. In this study, it can be seen that the implementation of Siskeudes in Kedung Jaya Village is running well and smoothly. Based on the analysis of the implementation model of George C. Edward III, which uses 4 indicators, communication, resources, disposition, and bureaucratic structure.